117k views
17 votes
What is the solution to the system of equations below?
y = 2x + 8
3(-2x + y)=12

User Kesava
by
5.4k points

1 Answer

7 votes

Step-by-step explanation:

There is inconsistency in the given statement and no solution

Step-by-step explanation:

y

=

2

x

+

2

x

y

=

8

,

Eqn (1)

3

(

2

x

+

y

)

=

12

6

x

+

3

y

=

12

2

x

y

=

4

Eqn (2)

It may be seen, L H S of equations (1) & (2) are same but not R H S.

Hence there is inconsistency in the given statement and no solution

User Weldabar
by
4.4k points